Efektivitas Komunikasi Penyuluhan Pertanian di Masa Pandemi Covid-19 terhadap Usahatani Padi Sawah di Desa Sulemandara Kecamatan Pondidaha Kabupaten Konawe - Ilang Selvia Jahudin; Ima Astuty Wunawarsih; Sitti Nur Isnian (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
The goal of this study is to see how efficient agricultural extension workers were in communicating with farmers during the Covid-19 epidemic on lowland rice farming in Sulemandara Village, Pondidaha District, Konawe Regency, knowledge of farmers in lowland rice farming during the Covid-19 pandemic in Sulemandara Village, Pondidaha District, Konawe Regency and the relationship between the effectiveness of the communication between the extension worker and the knowledge of the farmer in lowland rice farming. From November to January 2022, this study was done in Sulemandara Village, Pondidaha District, Konawe Regency with a population of 128 people and a sample of 32 respondents. Sampling in this study used a simple random sampling technique. Data analysis in this study used quantitative descriptive data analysis method with the formula of similarity of meaning. Communication between agricultural extension staff and farmers was found to be inefficient, according to the findings, namely that there were differences in meaning in communication between extension workers and farmers.